Validation and Reliability of the Instrument «Perception Scale of Physical Education Teacher´S Competencies in the Assistance of Disabled Persons» [Validación y Fiabilidad del Instrumento «Escala de Percepción de Competencias Docente en Educación Física en la Atención de Las Personas en Situación de Discapacidad»] - Aedo-Munoz, E; Merino-Munoz, P (Federacion Espanola de Docentes de Educacion Fisica, 2022)
The purpose of this study was to determine the degree of validity and reliability of the questionnaire Scale of Perception of Teaching Competence in Physical Education in the Attention of People with Disabilities (ECoDEFyD). The sample was of intentional type, in 37 teachers who teach Physical Education classes at the basic and high school level. The original instrument was modified based on the judgment of experts, and they approved its final use, reaching an acceptable content validity. The modified instrument achieved high internal consistency (α > 0.92) and excellent relative reliability (intra-class correlation coefficient = 0.962), demonstrating that the ECoDEFyD instrument is a valid and reliable instrument to measure the perception of competence and the most urgent needs in the face of the inclusion of students with permanent special educational needs, of Physical Education teachers, proving to be adequate to make decisions based on their results. © 2022 Federacion Espanola de Docentes de Educacion Fisica. All rights reserved.